PENIPUAN DALAM REKRUTMEN CALON BINTARA TNI AD: ANALISIS VIKTIMOLOGIS DAN PERLINDUNGAN KORBAN - Nabila Ramadhani; Ivan Zairani Lisi; Nur Aripkah (Universitas Labuhanbatu, 2026)
Fraud in the recruitment of prospective Indonesian Army (TNI AD) non-commissioned officers (Bintara), particularly through schemes promising guaranteed acceptance, has caused significant material and immaterial losses for victims. Beyond financial losses, victims often experience psychological impacts, including emotional distress, disappointment, and diminished self-confidence. This study aims to analyze such fraudulent practices from a victimological perspective and to examine the forms of legal protection available for victims. The research employs a socio-legal approach with qualitative methods, utilizing in-depth interviews with victims and supported by normative analysis of relevant legal frameworks. The findings reveal that victimological factors play a significant role in the occurrence of fraud, including high levels of trust in perpetrators, social pressure due to intense recruitment competition, and limited understanding of official recruitment procedures. In terms of victim protection, preventive and corrective measures are necessary, particularly through the reform of recruitment systems to ensure transparency, accountability, and the use of technology, alongside improving public legal awareness. This study underscores the importance of a victimological approach in understanding victim vulnerability and highlights the need to strengthen legal protection mechanisms to prevent fraud in military recruitment processes. Keywords: Fraud, Victimology, Victim Protection, Military Recruitment, TNI AD